2018
DOI: 10.1016/j.diamond.2018.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultraprecision polishing techniques on coherence times of shallow nitrogen-vacancy centers in diamond

Abstract: We investigate the correlation between surface roughness and corresponding T2 times of nearsurface nitrogen-vacancy centers (~7 nm/ 5 keV implantation energy) in diamond. For this purpose we compare five different polishing techniques, including both purely mechanical as well as chemical mechanical approaches, two different substrate sources (Diam2tec and Element Six) and two different surface terminations (O-and H-termination) during nitrogen-vacancy forming. All coherence times are measured and compared befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Braunbeck et al, reported that NV spin coherence times are independent of the surface finish. This result suggests that intrinsic sub-surface defects are playing a larger role in decoherence than the surface itself [236]. In contrast to NV center, SiV center emits a very narrow ZPL, typically less than 6 nm width at room temperature.…”
Section: Color Centres In Diamondsmentioning
confidence: 98%
“…Braunbeck et al, reported that NV spin coherence times are independent of the surface finish. This result suggests that intrinsic sub-surface defects are playing a larger role in decoherence than the surface itself [236]. In contrast to NV center, SiV center emits a very narrow ZPL, typically less than 6 nm width at room temperature.…”
Section: Color Centres In Diamondsmentioning
confidence: 98%
“…In contrast, Braunbeck et al studied the impact of mechanical polishing and etching techniques on coherence times for shallow emitters and found minimal correlation with surface roughness. 275 These findings suggest that the particular method of preparing flat diamond surfaces (i.e., etching, polishing, etc.) likely has a strong influence on the chemical termination.…”
Section: Surface Terminations For Increasing Nv Stabilitymentioning
confidence: 99%
“…When changing the H to the oxygen (O), fluorine (F) or nitrogen (N) with electronegativity higher than carbon, the dipole moment directed away from the diamond surface will be set up, and the diamond surfaces exhibit positive electron affinity (PEA). The experimental studies have showed that O-terminated [24][25][26] and F-terminated [27] diamond (100) surfaces can keep the negative charge state of shallow NV centers and increase the fluorescence intensity. However, for O-terminated nanodiamonds, blinking states (temporary intermittency in fluorescence) of NV centers was observed [28].…”
Section: Introductionmentioning
confidence: 99%